Conflict management strategies used by Portuguese nurse managers - Maria Manuela Martins; Leticia de Lima Trindade; Lara Vandresen; Simone Coelho Amestoy; Ana Paula Prata; Carlos Vilela (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: to analyze the perception and conflict management strategies used by nurses in the management of people in Portuguese health services. Methods: descriptive, correlational study, carried out in Portuguese health services, with an intentional non-probabilistic sample, totaling 95 nurse managers. A questionnaire and Conflict Management Scale were used, analyzing the variables of managerial activities and conflict management, with the aid of software. Results: it was identified that 60% of the managers, report having to mediate conflicts daily, and the majority report adopting dialogue in conduct. However, through the Kruskal-Wallis test, it was shown that enforcement strategies in conflict management prevail (p = 0.008), with collaborative ones being more restricted to monthly intervals (p = 0.049). Conclusions: managers perceive the importance of collaboration in the mediation of conflicts, however, in their daily lives; they tend to maintain imposing behaviors, signaling for a little transformational leadership style.